Reservoir Model Design A Practitioner's Guide - Ringrose, Philip; Bentley, Mark.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2015)
This book gives practical advice and ready to use tips on the design and construction of subsurface reservoir models. The design elements cover rock architecture, petrophysical property modelling, multi-scale data integration, upscaling and uncertainty analysis. Philip Ringrose and Mark Bentley share their experience, gained from over a hundred reservoir modelling studies in 25 countries covering clastic, carbonate and fractured reservoir types. The intimate relationship between geology and fluid flow is explored throughout, showing how the impact of fluid type, production mechanism and the subtleties of single- and multi-phase flow combine to influence reservoir model design. Audience: The main audience for this book is the community of applied geoscientists and engineers involved in the development and use of subsurface fluid resources. The book is suitable for a range of Master$1 (Bs level courses in reservoir characterisation, modelling and engineering.s
Preface -- Prologue -- 1. Model Purpose -- 2. The Rock Model -- 3. The Property Model -- 4. Upscaling Flow Properties -- 5. Handling Model Uncertainty -- 6. Reservoir Model Types -- 7. Epilogue -- Nomenclature -- Figure Credits -- Solutions -- Index.
Keywords: Earth sciences; Fossil fuels; Mineral resources; Geophysics; Engineering geology; Engineering -- Geology; Foundations; Hydraulics; Earth Sciences; Geophysics/Geodesy.; Mineral Resources; Geoengineering, Foundations, Hydraulics; Fossil Fuels (incl. Carbon Capture).; Electronic books